2017
DOI: 10.1158/1541-7786.mcr-16-0352
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 20q Amplification Defines a Subtype of Microsatellite Stable, Left-Sided Colon Cancers with Wild-type RAS/RAF and Better Overall Survival

Abstract: Here comprehensive analysis was performed on the molecular and clinical features of colorectal carcinoma (CRC) harboring chromosome 20q amplification. Tumor and normal DNA from patients with advanced CRC underwent next generation sequencing (NGS) via MSK-IMPACT and a subset of case samples were subjected to high resolution microarray (Oncoscan). Relationships between genomic copy number and transcript expression were assessed with The Cancer Genome Atlas (TCGA) CRC data. Of the CRC patients sequenced (n=401) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 21 publications
(25 reference statements)
2
27
0
2
Order By: Relevance
“…However, this result should be interpreted with caution since it was obtained for only two cell lines and has no statistical support. In CRC, the GNAS locus is frequently amplified which correlates with its increased mRNA expression (Ptashkin et al, 2017). Importantly, we previously observed a sig- Presence of 3C-Seq reads confirms the interaction of GNAS locus with rs6702619 region.…”
Section: Discussionsupporting
confidence: 63%
“…However, this result should be interpreted with caution since it was obtained for only two cell lines and has no statistical support. In CRC, the GNAS locus is frequently amplified which correlates with its increased mRNA expression (Ptashkin et al, 2017). Importantly, we previously observed a sig- Presence of 3C-Seq reads confirms the interaction of GNAS locus with rs6702619 region.…”
Section: Discussionsupporting
confidence: 63%
“…6). More recently, Ptashkin and colleagues (48) find that chromosome 20q amplification is associated with a better OS in LCC. In addition, because cetuximab is mainly used in advanced stages of colorectal cancer patients, FMGS mining is further conducted in four pathologic stages according to the American Joint Committee on Cancer standards.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have suggested that genes with CNAs are potential biomarkers and/or therapeutic targets for colorectal cancer. Therefore, detection and mapping of copy number abnormalities provide an approach for associating aberrations with disease phenotype and for localizing critical genes (4,5). It is importance to identify and functionally characterize novel genes with CNAs that are associated with colorectal cancer (4).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome 20q amplification has been commonly found in colorectal cancer and is involved in transforming adenoma to carcinoma (5,6). Chromosome 20q amplification is also a potential indicator of poor prognosis in patients with colorectal cancer (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%